Effect of glycemic control on mortality and infections in patients undergoing coronary artery bypass grafting: a Genesee County experience. Issue 2 (4th March 2019) - Khan, Mahin R.; Khan, Hafiz; Wahab, Ahsan; Chaudhary, Siddique; Munir, Ahmad; Youssef, John; Mocanu, Marian; Ríos-Bedoya, Carlos F.; Changezi, Hameem; Kesari, Kavitha
ABSTRACT: Background : We report post-coronary artery bypass outcomes and factors affecting the outcomes from the Genesee County, MI, where the population is distinctly characterized by a higher prevalence of renal failure (RF), diabetes, obesity and smoking than the national average. Methods : We performed a retrospective cohort study on 1133 patients undergoing isolated CABG at our hospital from June 2012 to July 2017. Primary outcome was the association between preoperative hemoglobin A1c (HbA1c) and all-cause postoperative mortality after CABG, secondary outcomes included the association between HbA1c and a composite of postoperative infections including sternal-wound infections, leg harvest-site infections, pneumonia or sepsis. Logistic Regression analyses were also performed. Results : There was no difference in the mortality rate (OR 1.0, 95% CI 0.4–2.3) and composite of all infections (OR 1.0, 95% CI 0.7–1.6) between the controlled (HbA1c ≤7%) and uncontrolled (HbA1c >7%) groups. However, RF (OR 5.9, 95% CI 1.5–22.9), smoking (OR 3.7, 95% CI 1.3–11.2) and ejection fraction <35% (OR 3.4, 95% CI 1.4–8.3) were independently associated with increased mortality after CABG. Additionally, low EF (OR 2.4, 95% CI 1.4–4.1) and smoking (OR 2.3, 95% CI 1.2–4.1) were associated with an increased rate of composite of all infections after CABG. Conclusion : Although not different in controlled and uncontrolled diabetic groups, mortality, in our population was associated with comorbidities like RF, smoking and congestive heart failure that are highly prevalent, emphasizing the need for interventions at primary care level to improve the postoperative outcomes after CABG.